The Effect of Discipline, Motivation and Compensation on Civil Servants' Performance at Ganesha University of Education - SUPADMI, Ni Nyoman Sri; SUARMANAYASA, I Nengah; RAHMAWATI, Putu Indah (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the influence of discipline, motivation, and compensation on the performance of civil servants (PNS) at the Ganesha University of Education. The research sample consisted of 145 respondents who were selected using a purposive sampling technique. Data was collected through a questionnaire which was then analyzed using multiple linear regression. The results showed that motivation had a significant positive effect on the performance of civil servants at the Ganesha University of Education. Meanwhile, discipline and compensation have no effect on the performance of civil servants at the Ganesha University of Education. Therefore, it is suggested that the management of the Ganesha University of Education pay special attention to the motivational aspect in improving the performance of their civil servants.